1987
DOI: 10.2307/3562663
|View full text |Cite
|
Sign up to set email alerts
|

In Death's Shadow: The Meanings of Withholding Resuscitation

Abstract: Many of the controversies surrounding the withholding of resuscitation are illuminated when we examine the language of resuscitation and resuscitative decisionmaking, and the contexts in which these decisions are made. Resuscitation and its withholding have multiple and often conflicting symbolic and emotional meanings for patients, families, and clinicians, and recognizing this divergence is essential to communication and to decisionmaking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Our survey showed about one‐quarter (27%) of Wisconsin long‐term care facilities have such a no‐CPR policy. The bases for a majority of these policies appear to be the poor success rate of CPR in this setting and the image of CPR as a symbol of unnecessary brutality 14 . We have no information about the use of similar “across‐the‐board” no‐CPR policies in other states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey showed about one‐quarter (27%) of Wisconsin long‐term care facilities have such a no‐CPR policy. The bases for a majority of these policies appear to be the poor success rate of CPR in this setting and the image of CPR as a symbol of unnecessary brutality 14 . We have no information about the use of similar “across‐the‐board” no‐CPR policies in other states.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic and acute conditions that are very common in the nursing home population (i.e., cancer, renal insufficiency (BUN > 50), cardiomyopathy, pneumonia, sepsis, and home‐bound condition) have been associated with CPR failure 2–4 . Such poor outcomes have led many health care providers to view CPR negatively, as a symbol of useless brutality when applied to frail individuals without any visible success 14 …”
mentioning
confidence: 99%
“…The ethics literature identifies many issues that are involved in decisions about whether to provide or withhold CPR. These include: the role of patient autonomy and the patient's contribution to the decision (Kerridge et al 1998); patients' and families' understanding of potential benefits and harms of CPR (Sears et al 2007;Marco and Larkin 2008); how well substitute decisionmakers are able to represent the patients' wishes (Wrigley 2007;Marks and Arkes 2008); doctors' lack of confidence discussing CPR (Menezes and Morgan 2008;Sulmasy et al 2008); the variability between doctors about whether to provide or withhold CPR for individual patients (Kelly et al 2002;Brims et al 2009;Tyrer et al 2009); variability between doctors about how they understand the role of the patient in the NFR decision (Kerridge et al 1998); futility (Ardagh 2000;Wreen 2004); and the meanings attached to CPR and therefore NFR (Nolan 1987). Guidelines have been developed to assist clinicians with this decision-making, including guidance for considering the ethical issues and for communicating CPR decisions (American Heart Association 2000; Baskett et al 2005;British Medical Association, Resuscitation Council (UK), and Royal College of Nursing 2007).…”
Section: Cpr Decisionsmentioning
confidence: 99%
“…In the present study this ambiguity showed up in those explanations which indicated that whether or not death was reversible was a matter of "time" or of "definition." Nolan (1987) has described this modern dilemma eloquently:…”
Section: Recent Developments In Adults' Conceptualization F Deathmentioning
confidence: 99%